Prediksi Kuat Tekan Beton Agregat Recycle Campuran Air Laut dengan Schmidt Rebound Hammer Test - Lusman Sulaiman; Ispianto; Muhammad Fahrizal Nur; Umar Hamzah Matottorang (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
Nowadays, using recyled aggregate and seawater as replacing natural aggregate and freshwater in mixing have been main priority to be a new concrete construction material. However, in order to asses their strength performance in fast and accurate, an appropriate method needs to be determined. Therefore, the aim of this research is to evaluate and predict the compressive strength of recycled aggregate concrete (RAC) mixed seawater using Schmidt rebound hammer test (SRH) and the result value was corresponded to concrete compressive testing machine (CTM) as control test of concrete specimens. Total 72 samples divided into three concrete mixtures were designed and prepared in cylindrical samples with w/c ratio of 0.45 and target compressive strength of 25 MPa. The first mixture was named natural aggregate concrete (NAC) or BAN as control concrete with 100% natural aggregate and fresh water. The second and third mixtures were named BAR-50 and BAR-100 with the BAN replacement of 50% and 100% RAC respectively. Seawater as mixing was performed in mixture concrete of BAR-50 and BAR-100. All sample mixtures were then wet cured at different age of 7, 28, 56 and 90 days in fresh water. The results show a good correlation between SRH and CTM tests with having high correlation of R2=0.9908. Also, a proposed mathematical model, equation 1, is created for quick calculation in predicting compressive strength of RCA. Therefore, the usage of SRH test is a realistic alternative to predict the compressive strength of recycled concrete with different percentage of replacement of NAC and mixing seawater.